Behind the blue and gray : the soldier's life in the Civil War - Ray, Delia (New York : Lodestar Books, 1991)
Traces, in this second of a three part series, the events of the Civil War from the first battle to the surrender with emphasis on the experiences of the individual soldier.
Includes index.
Includes bibliographical references.
Keywords: United States. -- Army -- History -- Civil War, 1861-1865 -- Juvenile literature; Confederate States of America. -- Army -- History -- Juvenile literature; United States. -- Army -- History -- Civil War, 1861-1865.; Confederate States of America. -- Army -- History; United States -- History -- Civil War, 1861-1865 -- Juvenile literature; United States -- History -- Civil War, 1861-1865.